Bitcoin As A Means of Transaction and Investment In The Perspective of Islam - Abdulloh Hamid; Anis Fittria; Ubbadul Adzkiya'; Santi Andriyani (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2021)
The emergence of bitcoin as a means of transaction and investment in the virtual world is intriguing to be studied. Many countries in the world have different perspectives upon the law of bitcoin itself. In Indonesia, the regulation on electronic money is in Indonesian Bank Regulation Number 20/6/PBI/2018 and MUI Fatwa Number 116/DSN-MUI/IX/2017. However, both have not specifically regulated bitcoin. As something new, bitcoin is necessary to be studied in the perspective of Islamic law. The research is a literature study utilizing content analysis to approach the data. The findings of the results are that bitcoin as a means of transaction is permissible (mubah) since there is a similar handover (taqabudh)–that there is a bitcoin to handover, there is no gambling (maisir), speculation (gharar), haram, riba, and false, and that the transactions is on a willingness basis (antharodin) of the both parties. Second, bitcoin as a means of transaction is haram if there is an uncertainty which is close to gharah and maisir, bitcoin as an investment tool has more damages than benefits.